Design optimization and generating characteristics of a linear arc PM vernier machine for wave energy conversion system - Urooj Jadoon; Faisal Khan; Salar Ahmad Khalil; Hatim Alwadie; Adoalateef Alzhrani (Results in Engineering)
Ocean wave energy offers a promising and sustainable pathway to convert mechanical energy into electricity. This research introduces novel linear arc machine topologies designed specifically for wave energy conversion systems to address critical challenges such as substantial cogging force, low power output, and size constraints. This study investigates optimized machine configurations by introducing two innovative designs incorporating varied permanent magnet volumes and slot-pole combinations and contrasting them with a conventional baseline. A genetic algorithm has been employed to refine geometric parameters, encompassing split ratio, permanent magnet volume, and rotor pole shape, to enhance average torque, output power, and efficiency. Comparative analysis with conventional designs revealed considerable improvements. Design M2 and M4 exhibited significant flux linkage enhancements (28.47 % and 32.50 %, respectively), while M1 and M3 demonstrated notable reductions in cogging force (37.16 % and 54.58 %, respectively). Additionally, M2 and M4 resulted in substantial reductions in copper and iron losses, leading to overall efficiency improvements. The optimized designs (M1-M4) achieved substantial gains in power generation and torque output, with up to 80 % higher power output and torque improvements ranging from 52 % to 65 %. Comparison analysis for evaluating performance metrics has been investigated for different stake lengths. These advancements highlight the potential of enhanced linear arc PM vernier machines for wave energy conversion systems. By mitigating cogging force, reducing losses, and improving power output, these designs contribute to more stable, efficient, and viable renewable energy solutions.